Improving CD3 bispecific antibody therapy in solid tumors using combination strategies - Lloyd, Katy; Middelburg, Jim; Ovcinnikovs, Vitalijs; Pencheva, Nora; Kemper, Kristel; van Hall, Thorbald (Frontiers in Oncology, 2025)
CD3 bispecific antibodies (bsAbs) are emerging as an important treatment option in the arsenal of oncologists. There are numerous FDA-approved CD3 bsAbs for both hematological and solid tumors. Despite these recent advances, the success of CD3 bsAbs in solid cancer has been hampered by hurdles like limited intratumoral T cell numbers, immunosuppressive tumor microenvironments (TME), and poor memory T-cell induction. Furthermore, tumor surface antigen selection for an optimal therapeutic window and acceptable collateral damage to normal tissues is challenging. In this review, we discuss recent research investigating combination approaches aimed at improving CD3 bsAb efficacy in solid cancer.